Implementación de un sistema de costos por procesos de la empresa “Isaflower” del municipio de Belén Boyacá – estudio de caso (2021)
The relevance of implementing a well-structured cost system within a company serves to ensure rigorous control of the activities carried out; Furthermore, it is presented as an interesting solution to avoid the misuse of resources, unnecessary costs are avoided, it facilitates decisionmaking, minimizes risks and in itself makes the entity efficient and effective in the development of its corporate purpose. It should be clarified that cost systems go hand in hand with the production process of the company and that is why in rose crops it turns out to be necessary a process cost system, this ensures greater profitability, benefits, important solutions and in if any risk arises, it can be mitigated. It is noteworthy that, if you want to position, contribute to the growth and expansion of a company in the market, generate more profits, obtain greater results, it is necessary to manage cost accounting as a growth strategy, in order to record and analyze the movements of the entity and thus obtain a useful decision-making from the information obtained.